Implementasi Reforma Agraria pada Masa Orde Lama dan Reformasi - Vindria Shafa Clarissha1; Recca Ayu Hapsari; Nada Alia Husna; M Argo Renaldo (Universitas Batanghari Jambi, 2020)
Reform is a method to solve agrarian problem for economic inequality of population income in Indonesia. and the food and ruler and landlord are well resolved so that the economic progress of the nation can be evenly and well-being achieved. The policy taken by the state leaders must comply with the interests of all Indonesian citizens without discriminate or their policies should be the same as the principles of applicable law. And the reform of the reforms in the old order and the Reformation is certainly. A way to create a responsive policy that can coordinate interest. All citizens but in different ways are most important in running. A policy remains to be based on the provisions of the law due to Indonesia state law under the UUD 1945, in making the concept of agrarian policy in order to walk with. Should involve scientists, officers, activists, and also elements of society.